(untitled) (KULT_online, 2022)
The Child Sex Scandal and Modern Irish Literature: Writing the Unspeakable by Joseph Valente and Margot Gayle Backus uses the concept of the ‘enigmatic signifier’ to scrutinize the portrayals of children’s traumatic first sexual experiences in modern Irish literature. It is a daring and unapologetic book that investigates both the private and collective reactions to pedophilia and argues for literature’s superiority over the press in dealing with traumatic experiences.